How to Love : Graphic Novellas by Actus Comics (Merian, 2011)
Summer story / Batia Kolton -- L’elixir d’amour / David Polonsky -- Independence day / Mira Friedmann -- Love love love / Itzik Rennert -- Your number one fan / Rutu Modan -- 8:00 to 10:00 / Yirmi Pinkus